Pump : a natural history of the heart - Schutt, Bill (Algonquin Books of Chapel Hill, 2021)
"Zoologist Bill Schutt delivers a look at hearts from across the animal kingdom, from insects to whales to humans. Illustrated with black-and-white line drawings"--